Kuat Tekan Dan Porositas Beton Semen OPC, PCC, Dan OPC POFA Di Lingkungan Gambut - Sitompul, Iskandar Romey; Pradana, Tomy; Olivia, Monita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This research study the compressive strength and porosity of concrete OPC cement, concrete PCC cement, and concrete with made by combine of OPC+10% palm oil fuel ash (POFA) cement. The specimens cured in distilled water for 28 days. Then specimens were immersed ini peat environment until 28 days. This research result show there was an increase of compression strength of the concrete with made combine of OPC+10% palm oil fuel ash (POFA) cement and concrete PCC cement after 28 days immersed in peat environment. The percentage of porosity for of concerete OPC cement immersed in peat environment increased compared to the speciemens immeresed in distilled water. For concrete with combine of OPC+10% palm oil fuel ash (POFA) cement and concerete PCC cement decreased after immersed in peat environment. The test result revealed that durability of OPC+10%POFA concrete and PCC concrete in peat environment the well of OPC concrete.Keywords: OPC, PCC, palm oil fuel ash(POFA), peat area